Evaluation Of Different Essential Oils Against Fusarium Oxysporum F. Sp. Lycopersici And Sclerotium Rolfsii Causing Wilt And Collar Rot Diseases In Tomato And Brinjal (Journal of Plant Disease Sciences, 2021)
Tomato (Lycopersicon esculentum Mill) and Brinjal (Solanum melongena L.) are most widely cultivated vegetable fruit crops. In vitro efficacy of essential oils against Fusarium oxysporum f.sp. lycopersici and Sclerotium rolfsii Sacc. were tested @ 2500 and 3000 ppm. At 2500 ppm, Rose oil and Lavender oil were found best effective which inhibited 94.44 per cent mycelial growth of Fusarium oxysporum f.sp. lycopersici, whereas, at 3000 ppm, Rose oil, Clove oil and Lavender oil were found best which inhibited 94.44 per cent mycelial growth of Fusarium oxysporum f.sp. lycopersici. Similarly in case of brinjal, at 2500 ppm, Clove oil and Lavender oil were found most effective which inhibited 94.44 per cent mycelial growth of Sclerotium rolfsii, whereas, at 3000 ppm, Rose oil, Clove oil, Citronella oil and Lavender oil were found best which inhibited 94.44 per cent mycelial growth of Sclerotium rolfsii.
Keywords: Brinjal; Essential oils; usarium oxysporum f.sp. lycopersici; clerotium rolfsii Sacc; Tomato